Absent pericardium and lung hypoplasia in a child with severe mitral regurgitation. (September 2020) - Khazi, Fayaz Mohammed; Abdel Aziz, Tarek; Siddiqi, Nayyer R; Karaly, Yehia; Aljassim, Obaid; Al Halees, Zohair Yousef
An 8-year-old girl with severe mitral regurgitation presented with symptoms of heart failure. Clinical investigations did not raise suspicion of an absent left pericardium. Congenital defects of the pericardium are rare and frequently associated with other cardiac lesions. We describe a case of severe mitral regurgitation in a child in whom an absent left-sided pericardium with hypoplasia of left lung was found incidentally during surgery to repair the mitral valve. We believe such associations with other heart diseases is usually circumstantial but can influence the perioperative morbidity, length of hospital stay, and even alter the surgical management.